Modelling And Simulation Of A Wind Turbine With Doubly Fed Induction Generator In Full Load Operation - Hussin, Mohamed Saiful Firdaus; Mohd Yassim, Halyani; Zainon, Maslan; Ahmad, Emy Zairah; Idris, Norain (Asian Research Publishing Network (ARPN), 2018)
The paper focuses on modelling and simulation of a 5 MW wind turbine with doubly fed induction generator (DFIG) in full load operation. The wind turbine model is described mathematically and presented in simulation blocks. Through a computer simulation, the wind turbine behavior in full load operation is investigated. A speed controller is used to adjust the pitch angle of a rotor blade in high wind speed to limit the wind energy captured by the turbine to the nominal power value. By adjusting the pitch angle to 18.26° at wind speed 20 m/s, the wind turbine is protected from mechanical damage due to torque and power limitation. The simulation results obtained can be used as references for future optimization for the variable speed wind turbine operation.